Bioassay-guided isolation of a Mycobacterium tuberculosis bioflim inhibitor from Arisaema sinii Krause. (January 2019) - Jiang, Chang-He; Gan, Meng-Lan; An, Ting-Ting; Yang, Zai-Chang
Abstract: Mycobacterium tuberculosis biofilms harbour drug-tolerant bacteria. Identification of drugs that inhibit biofilm formation could enable the dramatic shortening of tuberculosis treatments using standard antibiotics. Arisaema sinii Krause is used to treat pulmonary and lymphatic tuberculosis by Dong People of China. Current study was aimed to purify the active components against M. tuberculosis biofilms from Arisaema sinii extract by using bioassay-guided isolation. ( E )-2-(methyl (phenyl) amino) ethyl 2-(2-hydroxyundecanamido)-7, 11-dimethyl-3-oxotetradec-4-enoate, compound1, was identified as the active component. It could inhibit mycobacterial biofilm formation, disperse the preformed biofilms, and disrupt the mature biofilms at concentration of 4, 8, and 32 μg/ml, respectively. At the dose of 32 μg/ml, it could potentiate the bactericidal activity of isoniazid against M. tuberculosis in mature biofilms. The results of this study indicate that compound1 might be a novel lead compound against mycobacterial biofilm formation. Graphical abstract: Highlights: Compound1 was isolated from Arisaema sinii for the first time. Compound1 could inhibit mycobacterial biofilm formation, disperse the preformed. biofilms, and disrupt the mature biofilms in a dose-dependent manner. Compound1 might be a novel lead compound against mycobacterial biofilm formation.